2022
DOI: 10.1093/jxb/erac375
|View full text |Cite
|
Sign up to set email alerts
|

Distinct chemical resistance-inducing stimuli result in common transcriptional, metabolic, and nematode community signatures in rice root and rhizosphere

Abstract: Induced resistance (IR), a phenotypic state induced by an exogenous stimulus and characterized by enhanced resistance to future (a)biotic challenge, is an important component of plant immunity. Numerous IR-inducing stimuli have been described in various plant species, but relatively little is known about ‘core’ systemic responses shared by these distinct IR stimuli and the effects of IR on plant-associated microbiota. In this study, we foliarly applied four distinct IR stimuli (β-aminobutyric acid, acibenzolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Although used at different doses, DHA and PA induce similar kinds of host IR responses, such as the activation of ROS metabolism, SA, and the diterpenoid phytoalexin pathway (Chavan et al 2022 ; Desmedt et al 2021 , 2022b ). Desmedt et al ( 2022a ) showed that distinct IR stimuli viz., BABA, ASM, DHA, and PA, capable of inducing systemic IR in rice against the RKN M. graminicola , share common transcriptional responses such as the induction of JA and phenylpropanoid pathway metabolism in the systemic tissues. The compatibility of DHA and PA shows great scope for this combination treatment to evaluate for a broad spectrum of stresses in rice.…”
Section: Discussionmentioning
confidence: 99%
“…Although used at different doses, DHA and PA induce similar kinds of host IR responses, such as the activation of ROS metabolism, SA, and the diterpenoid phytoalexin pathway (Chavan et al 2022 ; Desmedt et al 2021 , 2022b ). Desmedt et al ( 2022a ) showed that distinct IR stimuli viz., BABA, ASM, DHA, and PA, capable of inducing systemic IR in rice against the RKN M. graminicola , share common transcriptional responses such as the induction of JA and phenylpropanoid pathway metabolism in the systemic tissues. The compatibility of DHA and PA shows great scope for this combination treatment to evaluate for a broad spectrum of stresses in rice.…”
Section: Discussionmentioning
confidence: 99%
“…Plant disease resistance is dependent on both pre-existing physical and chemical barriers associated with plant-innate immunity and plant-induced immunity, where signalling molecules activate the defence response to protect plant tissues from damage caused by biotic or abiotic stresses [ 1 , 2 ]. In the absence of any pathogen attack, these defence mechanisms may be induced by physical or chemical elicitation [ 3 , 4 ], resulting in enhanced resistance to pathogens and diseases and tolerance to abiotic stress and adversity. In fact, defence priming supports a faster, stronger and more sustained response to stresses [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%